A STUDY ON SURGICAL MANAGEMENT OF MONTEGGIA FRACTURE-DISLOCATION IN ADULTS - D, NARENDER; KATRAVATH, LALUNAIK; T, PARAMESHWARI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to study the functional outcome of Monteggia fracture-dislocation in adults by surgical management. Open reduction and internal fixation of the ulna with dynamic compression plate and screws not only prevent malunion or non-union but also achieve rapid union of the fracture site. Methods: Twenty cases of simple Monteggia fracture-dislocation in adults were treated by open reduction and internal fixation with a minimum six-holed AO 3.5 mm dynamic compression plate of the ulna with closed reduction of the radial head. In a case with a delayed presentation, the radial head was removed. The follow-up ranged from 5 to 15 months. Results: Right elbow affliction was more common in males than left. The majority of fracture-dislocation cases resulted from auto accidents. With an average age of 35.9 years, fracture dislocations were more prevalent in the third and fourth decades of life. According to Bado’s categorization, Type 1 fracture-dislocation accounted for the majority of the cases. To avoid radial head redislocation, the upper limb was immobilized with the elbow flexed 110–120° and the forearm supinated. We had 13 (65%) instances with great results using the Anderson et al. grading system, six (30%) with good results, one (5%) with bad results, and no cases with failure. The only problems were a superficial infection and posterior interosseous nerve damage, both of which healed on their own when the radial head dislocation was closed down and the ulna was internally fixed with an AO 3.5 mm dynamic compression plate. Conclusions: Adults with Monteggia fracture-dislocation can be treated simply and effectively with a high level of functional result utilizing the approach of early closed reduction of the radial head and open reduction and internal fixation of the ulna using a minimum of six holes AO 3.5 mm dynamic compression plate.